Faktor Penyebab Ketidaklengkapan Pengisian Resume Medis Pasien Rawat Inap di Rumah Sakit - Alifah, Safira Nur; Santi, Maya Weka; Rachmawati, Ervina; Sabran, Sabran (FORIKES, 2022)
Incomplete medical resumes are one of the factors that influence hospital quality and service improvement, which can have an impact on reducing the quality of hospital services, administrative needs and fulfilling patient rights and safety. So a study is needed that aims to find out the factors that cause incomplete medical resume filling for inpatients at the hospital. The method in this study is a literature review using the Google Scholar database, Crossreff, Garuda Portal and Directory of Open Access Journal as many as 20 articles that meet the criteria. The results of the review show that the incomplete filling out of medical resumes is caused by the implementation of standard operating procedures that has not been maximized, doctors' time is tight, monitoring and evaluation has not been maximized, socialization of standard operating procedures has not been maximized, attitudes and behavioral problems of doctors, lack of understanding and knowledge of doctors, lack of understanding and knowledge medical recorders, shortage of medical recorders, no assembly room available, standard operating procedures not yet available, standard operating procedures not yet detailed, lack of reward/punishment, no incomplete recapitulation, and limited funding sources. The dominant factor causing incomplete medical resumes is the implementation of standard operating procedures that has not been maximized.Keywords: medical resume; incompleteness; inpatient; hospital ABSTRAK Ketidaklengkapan resume medis merupakan salah satu faktor yang berpengaruh terhadap menaikkan mutu dan pelayanan rumah sakit, yang dapat berdampak pada penurunan mutu pelayanan rumah sakit, keperluan administrasi serta pemenuhan hak dan keselamatan pasien. Maka diperlukan studi yang bertujuan untuk mengetahui faktor penyebab ketidaklengkapan pengisian resume medis pasien rawat inap di rumah sakit. Metode pada studi ini adalah literature review menggunakan database Google Scholar, Crossreff, Portal Garuda dan Directory of Open Access Journal sebanyak 20 artikel yang memenuhi kriteria. Hasil review menunjukkan bahwa ketidaklengkapan pengisian resume medis disebabkan oleh pelaksanaan standar operasional prosedur belum maksimal, waktu dokter padat, monitoring dan evaluasi belum maksimal, sosialisasi standar operasional prosedur belum maksimal, sikap dan masalah perilaku dokter, kurangnya pemahaman dan pengetahuan dokter, kurangnya pemahaman dan pengetahuan perekam medis, kekurangan perekam medis, tidak tersedia ruang assembling, standar operasional prosedur belum ada, standar operasional prosedur belum rinci, kurangnya reward/punishment, belum ada rekapitulasi ketidaklengkapan, dan sumber dana terbatas. Faktor dominan penyebab ketidaklengkapan resume medis adalah pelaksanaan standar operasional prosedur belum maksimal.Kata kunci: resume medis; ketidaklengkapan; rawat inap; rumah sakit